Value of office hysteroscopy and simultaneous endometrial sampling performed on day 21 preceding IVF cycle in patients given GnRH agonist long protocol - Kumbak, B.; Sahin, L.; Ozkan, Z. S.; Atilgan, R.; Simsek, M.; Sapmaz, E. (Oxford Univ Press, 2012)
[Abstract Not Available]
28th Annual Meeting of the European-Society-of-Human-Reproduction-and-Embryology (ESHRE) -- JUL 01-04, 2012 -- Istanbul, TURKEY